Pengaruh resiko kredit terhadap profitabilitas bank (Studi pada Bank Mandiri, Bank BNI dan Bank BRI) - Suhartono, Suhartono; Ai Halimah; Taat Kuspriyono; Abdurrachman; Lukman Hakim; Vera Agustina Yanti (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
This research is motivated by Credit Risk and Profitability that occurs in National Banks, namely Bank BRI, Bank Mandiri, and Bank BNI in 2012 - 2021. This study analyzes the effect of credit risk using Non Performing Loans (NPL) while profitability uses Return On Assets (ROA). ). The research method is descriptive quantitative with observations and analytical techniques used are classical assumption test and simple linear regression test. The data used is secondary data obtained from the financial statements of Bank BRI, Bank Mandiri and Bank BNI. The sample used in this study amounted to 30 samples from 3 national banks with a total period of 10 years for each bank. The results showed that there was an influence of the credit risk variable (NPL) on profitability (ROA) with an effect of 0.729 or 72.9%. T test shows that NPL has a significant negative effect on ROA and the hypothesis is accepted. If the NPL rises, it will reduce profitability. The novelty of this research is that there are comparisons from several banks and the latest data observation period is 2012-2021.